Gaya Kepemimpinan Lurah dalam Meningkatkan Motivasi Kerja Perangkat Lurah pada Kelurahan Tuan Kentang - Ristasari Ristasari; Maulana Maulana; Alamsyah Alamsyah (Sekolah Tinggi Ilmu Administrasi (STIA) Yappi Makassar, 2024)
Ritasari. This study aims to analyze the leadership style of the village head in increasing the work motivation of the village head in Tuan Kentang Village. The study used qualitative methods with data collection, namely observation, interviews and documentation. The results showed that the leadership style of the village head of Tuan Kentang village had no signs that indicated an authoritarian leadership style, because in this case the employee was given the freedom to work even though he still had to comply with the main tasks and functions, on the other hand the Lurah was also a leader capable of employee morale. to work. The leadership style of Tuan Kentang Village also includes a delegative leadership style that is able to delegate work and is authorized in accordance with the main tasks and functions. The leadership style of Kelurahan Kentang, which is more participatory, makes employees feel happy to work better, one of which shows that Kelurahan Kentang uses a participatory leadership style, namely discussions, exchanging ideas and meetings held before the activity. Supporting factors in terms of coordination between superiors and staff and related institutions are very good and run as expected, this can be seen from meeting activities. In addition, the village head of Tuan Kentang as a leader is able to set an example and motivate employees to improve their performance for the better. The inhibiting factor for the Lurah's leadership style in motivating employees in Tuan Kentang Village is the lack of performance supporting facilities and infrastructure, namely the work room and service room that is not so, and less supported, such as computers and printers to support administrative services. In principle, the existence of complete facilities and infrastructure can increase employee work motivation for the better.